Ischemic Preconditioning and Iloprost Reduces Ischemia-Reperfusion Injury in Jejunal Flaps: An Animal Model - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Background: Free jejunal flaps are among the most commonly used flaps for esophageal reconstruction. However, ischemia-reperfusion injury caused by warm ischemia seen during transfer limits their use. Iloprost, a prostacyclin analogue, has been shown to reduce ischemia-reperfusion injury in various organs. The authors investigated tissue damage in jejunal flaps with iloprost and ischemic preconditioning and compared the effectiveness of these two modalities. Methods: Thirty-four Sprague-Dawley rats were randomized into five groups: sham, ischemia-reperfusion (control), ischemic preconditioning, iloprost, and ischemic preconditioning plus iloprost. All flaps, except those in the sham group, underwent ischemia for 60 minutes and reperfusion for 2 hours. Flap perfusion was assessed by laser Doppler perfusion monitoring. Histologic sections were scored using the Chiu scoring system. Superoxide dismutase and myeloperoxidase levels were measured spectrophotometrically. Results: Animals that were administered iloprost and/or underwent ischemic preconditioning had better postischemic recovery of mesenteric perfusion (ischemic preconditioning, 78 percent; iloprost, 83 percent; ischemic preconditioning plus iloprost, 90 percent; versus ischemia-reperfusion, 50 percent; p < 0.05). All intervention groups showed improved histology of jejunal flaps following ischemia-reperfusion injury (ischemic preconditioning, 3; iloprost, 2.3; ischemic preconditioning plus iloprost, 3.2; versus ischemia-reperfusion, 4.7; p < 0.01, p < 0.001, and p < 0.05, respectively). Superoxide dismutase levels were higher in ischemic preconditioning, iloprost plus ischemic preconditioning, and iloprost groups (ischemic preconditioning, 2.7 +/- 0.2; ischemic preconditioning plus iloprost, 2.5 +/- 0.3; versus ischemia-reperfusion, 1.2 +/- 0.1; p < 0.01; iloprost, 2.4 +/- 1.1; versus ischemia-reperfusion, 1.2 +/- 0.1; p < 0.05). Myeloperoxidase, a marker for neutrophil infiltration, was lower in the iloprost group (iloprost, 222 +/- 5; versus ischemia-reperfusion, 291 +/- 25; p < 0.05). Conclusions: This study showed that both iloprost and ischemic preconditioning reduced reperfusion injury in jejunal flaps. Based on histologic results, iloprost may be a novel treatment alternative to ischemic preconditioning.
Keywords: SKIN FLAPS; RECONSTRUCTION; PROSTACYCLIN; TOLERANCE; VIABILITY; INTESTINE; SURVIVAL; IMPACT